ECONOMIC POLICY UMAR BIN KHATTAB - M. Aufarul Mawahib (Universitas Islam Negeri Mataram, 2019)
Umar bin Khattab during his leadership in the city-state of Medina he had laid the foundations of the modern state especially in the economic field which will be discussed in this paper. Umar made many breakthroughs that had never been done by the Messenger of Allah and the Caliph before, Abu Bakr as-Siddiq. Although one of the policies that will be mentioned in this paper is opposed by some Muslims at that time, Umar can prove to his people that what he did was for the common good and interests.